A new analysis of the MiniBooNE low-energy excess - C. Giunti; A. Ioannisian; G. Ranucci (Journal of High Energy Physics, 2020)
Abstract We present the results of a new analysis of the data of the MiniBooNE experiment taking into account the additional background of photons from ∆+/0 decay proposed in ref. [1] and additional contributions due to coherent photon emission, incoherent production of higher mass resonances, and incoherent non-resonant nucleon production. We show that the new background can explain part of the MiniBooNE low-energy excess and the statistical significance of the MiniBooNE indication in favor of short-baseline neutrino oscillation decreases from 5.1σ to 3.6σ. We also consider the implications for short-baseline neutrino oscillations in the 3+1 active-sterile neutrino mixing framework. We show that the new analysis of the MiniBooNE data indicates smaller active-sterile neutrino mixing and may lead us towards a solution of the appearance-disappearance tension in the global fit of short-baseline neutrino oscillation data.